By Dint of History: Ways in which social work is (re)defined by historical and social events - Jonathan Parker; Magnus Frampton (Social Work and Society)
This paper examines aspects of the historico-political development of social work in the UK and Germany, acknowledging some of the contested aspects of historical analysis. The article examines four core areas in which social work has adapted to the influence of historical events - the English Poor Laws, political turmoil and the rise of National Socialism in Germany, the turn towards indigeneity in contemporary practice, and the increasing populism and politicisation in care across both countries. These are understood in terms of power and the discourses created through social, political and historical change.